2017
DOI: 10.1017/s0308210516000433
|View full text |Cite
|
Sign up to set email alerts
|

Surface energies emerging in a microscopic, two-dimensional two-well problem

Abstract: In this article we are interested in the microscopic modeling of a twodimensional two-well problem which arises from the square-to-rectangular transformation in (two-dimensional) shape-memory materials. In this discrete set-up, we focus on the surface energy scaling regime and further analyze the Hamiltonian which was introduced in [KLR15]. It turns out that this class of Hamiltonians allows for a direct control of the discrete second order gradients and for a one-sided comparison with a two-dimensonal spin sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…In dimension two, the analysis was extended to the frame-indifferent linearized setting by S. Conti and B. Schweizer in [20] who also accomplished the characterization of the fully nonlinear framework (1.3) for d = 2 in the two subsequent papers [19,21]. Recently, some related microscopic models for twodimensional martensitic transformations as well as their discrete-to-continuum limits have been analyzed in [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…In dimension two, the analysis was extended to the frame-indifferent linearized setting by S. Conti and B. Schweizer in [20] who also accomplished the characterization of the fully nonlinear framework (1.3) for d = 2 in the two subsequent papers [19,21]. Recently, some related microscopic models for twodimensional martensitic transformations as well as their discrete-to-continuum limits have been analyzed in [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…In [15] it is shown that the Γ-limit of (0.6) is an interfacial energy concentrated on the jump set of ∇u. A microscopic derivation of such result has been recently obtained in [18] in the context of squareto-rectangular martensitic phase transitions. We point out that in [15,18] the two wells of K consist of matrices with positive determinant, while this is not the case in the present context.…”
Section: Introductionmentioning
confidence: 91%
“…Remark 7. Then there exists a constant C < ∞ and a sequence ( (34). Set E := lim sup ε↓0 E ε (ω; u ε , A).…”
Section: Outline Of the Proof Of Theorem 31mentioning
confidence: 99%